Attitude of Agricultural Stakeholders on Use of Short Message Service (SMS) in Transfer of Technology - Sangeetha, V.; Burman, R. Roy; Dubey, S. K.; Sharma, J.P.; Singh, Ishwari (Indian Journal of Extension Education, 2015)
The goal of Information and Communication Technology (ICT) is to provide the benefits of information revolution to the  rural masses by enhancing farming efficiency, farm productivity and farmers' income. In order to bring knowledge  empowerment of rural people and to increase agricultural productivity, cyber extension centers were established in  Sidhauli and Kasmanda blocks of Sitapur district of Uttar Pradesh under “Cyber Extension Model for Agricultural  Development: An Action Research project”. In order to strengthen the information base of the farmers and to bridge the  information gap, SMS was sent to the farmers from project location. In this background, a study was conducted in Sidhauli  and Kasmanda block of Sitapur district of Uttar Pradesh among 80 farmers (40 in each block), 20 Krishi Vigyan Kendra (KVK) and State Agriculture Department (SAD) officials and 20 post office personnel to find out ease of use, usefulness  and attitude towards SMS. The findings revealed that seventy per cent farmers, 100 per cent KVK and 100 per cent post  office personnel were having mobile phones. It was also found that 55 per cent of farmers and all post office and KVK  personnel strongly agreed with the point that SMS was fast, easy to understand and follow. Action taken results showed  that 80 per cent of the farmers and 100 per cent of post office and KVK personnel opened the message up, 80 per cent of the  farmers, 100 per cent of post office and KVK personnel read the contents of the message, 60 per cent of the farmers  utilized the message and 30 per cent of the farmers and 90 per cent of post office and KVK personnel spread the message  among the farmers. The findings had shown that SMS played a substantial role in bridging the agricultural information  gap in the rural area.
Keywords: Mobile phone; SMS; ease of use; attitude towards SMS